Analisis Alokasi dan Pengelolaan Dana Bagi Hasil Cukai Hasil Tembakau (DBHCHT) di Kabupaten Kudus Tahun Anggaran 2010-2012 - Bayu Nugroho; Purwoko .; Nunik Retno H (Journal of Politic and Government Studies, 2015)
This Research carried out with the aim background knowledge management and allocation of funds for Excise tobacco results (DBHCHT) in Kudus District fiscal year 2010-2012. Funds for Excise tobacco results (DBHCHT) is one of the fund given by the central government to the local government from the State Budget with percentage division based on the regional potential and a benchmark for PMK 84/PMK.07 /2008 and subsequent changes in PMK No. 20/PMK.07 /2009 about the use DBHCHT and sanctions on abuse of Allocation DBHCHT.This research uses two methods or that is a combination of quantitative methods and the method qualitative research method also called descriptive analytical mind. This research subject that is the parties involved in managing DBHCHT is The overall Regional Secretary Kudus Regency, Economics district Sanctuary and service agencies SKPD on that are involved in the management of DBHCHT. Technical data collection on an interview, documentation, literature and then analyzed through techniques examine, editor data, editing, presentation data in the form table and draw conclusions.This research that is technically allocation and management of the funds for Excise tobacco results (DBHCHT) in Kudus District fiscal year 2010-2012 if it is seen as a model guidelines based on the regulation of the Minister of Financial No 84/PMK.07 /2008 and its amendments No 20/PMK.07 /2009 was appropriate and quite well but effective and efficient in the use of the funds are still less optimal. From the result of the research found many obstacle faced by the manager of DBHCHT such as timeliness in the preparation, implementation, reporting, the clarity of the regulation is not appropriate for the conditions of problems in field.